Parecoxib Reduced Postsurgical Pain and Facilitated Movement More Than Patient Controlled Analgesia - Chiu, Szu-Ching; Livneh, Hanoch; Chen, Jin-Cheng; Chang, Chia-Ming; Hsu, Honda; Chiang, Tsay-I; Tsai, Tzung-Yi (Frontiers in Surgery, 2022)
Background: Postoperative pain management is an imperative issue for patients undergoing lumbar spinal fusion surgery. Delayed pain relief is associated with poor clinical outcomes. This study compared the effects of intravenously administered patient-controlled analgesia (PCA) with intravenous parecoxib, both commonly used methods for analgesic pain control after surgery. Methods: A non-randomized study was used to recruit 68 patients who were scheduled to receive lumbar spinal fusion surgery at a hospital in Taiwan from April through December of 2020. The group treated with parecoxib received an initial perioperative dose of parecoxib 40 mg during a 30-minute period and then postoperative intravenous parecoxib at 40 mg per 12-hour period, for 72 hours. Those with PCA received morphine (0.4 mg/ml), droperidol (0.02 mg/ml), diphenhydramine (0.48 mg/ml), midazolam (0.02 mg/ml) and saline solution during the 3-day study course. Major outcomes, including visual scale pain score and Barthel index of activities of daily living, were collected via review of medical records at 4 times: 12, 24, 48 and 72 hours after surgery. Comparative effects between two groups were assessed by the generalized estimating equations. Results: After adjusting for potential confounders, the administration of parecoxib was associated with a significant decrease in pain scores and an increase in the Barthel Index, when compared with the PCA group (all p < 0.05). Notably, both effects would maintain for 72 hours after surgery. Discussion: This is the first trial of which the authors are aware, that supports intravenous parecoxib as significantly enhancing patient mobility, in addition to having pain control efficacy, when compared with PCA. This study could be used as a reference when instituting interventions to improve the adaptation process and clinical prognoses after lumbar spinal fusion surgery.